Left ventricular remodelling in patients with arterial hypertension and excess salt consumption - V. S. Volkov; O. B. Poselyugina; S. A. Nilova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study left ventricular (LV) remodelling features in patients with arterial hypertension (AH) and excess salt consumption. Material and methods. In total, 440 patients with essential AH and no clinically manifested heart failure were examined: 230 with no AH complications and 210 with myocardial infarction (MI) 6 months ago or earlier. In all participants, assessment of salt taste sensitivity threshold (STST) and 24-hour sodium excretion with urine, echocardiography and 24-hour blood pressure (BP) monitoring were performed. Results. The majority of AH patients had excessive salt consumption. In AH individuals with high STST and salt consumption >16 g/d, a specific LV remodelling type was observed, characterised by increased end-diastolic volume and myocardial mass. Conclusion. The main cause of LV remodelling in AH patients could be volume overload, due to excess salt consumption.